Towards a thoracic conductive phantom for EIT. (March 2020) - de Gelidi, Serena; Seifnaraghi, Nima; Bardill, Andy; Wu, Yu; Frerichs, Inéz; Demosthenous, Andreas; Tizzard, Andrew; Bayford, Richard
Highlights: Carbon filled thermoplastic polyurethane was used to generate a conductive phantom. An anatomically accurate model can be 3D printed once the above filament is used. The model is slightly deformable under finger pressure. Successful preliminary in vitro study for Electrical Impedance Tomography. Abstract: Phantom experiments are a crucial step for testing new hardware or imaging algorithms for electrical impedance tomography (EIT) studies. However, constructing an accurate phantom for EIT research remains critical; some studies have attempted to model the skull and breasts, and even fewer, as yet, have considered the thorax. In this study, a critical comparison between the electrical properties (impedance) of three materials is undertaken: a polyurethane foam, a silicone mixture and a thermoplastic polyurethane filament. The latter was identified as the most promising material and adopted for the development of a flexible neonatal torso. The validation is performed by the EIT image reconstruction of the air filled cavities, which mimic the lung regions. The methodology is reproducible for the creation of any phantom that requires a slight flexibility.